Bodily symptoms: new approaches to classification. - Sharpe, M; Mayou, R; Walker, J (2006)
OBJECTIVE: To examine the current approach to classifying bodily symptoms in both psychiatry and medicine and to suggest better alternatives. METHODS: Theoretical analysis, narrative review, and theoretical proposal. RESULTS: The assumptions that (a) bodily pathology can always explain bodily symptoms, (b) psychopathology can always explain bodily symptoms in the absence of bodily pathology, and (c) dichotomizing bodily symptoms into "medical" and "psychiatric" types is clinically useful were all found to have questionable validity and utility. CONCLUSION: Alternative multiaxial diagnostic approaches for the classification of bodily symptoms are proposed. These are intended to (a) give greater prominence to bodily symptoms in their own right, (b) allow etiology to be conceptualized in terms of multiple factors, and (c) provide the basis for integrating medical and psychiatric approaches to patient care.